1998
DOI: 10.1038/sj.bjp.0701838
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of nitric oxide to cardiovascular status and responses to vasodilators in conscious, hypertensive, transgenic ((mRen‐2)27) rats

Abstract: 1 The aim of the study was to measure the regional haemodynamic responses to vasodilators, and the eects of nitric oxide (NO) synthase inhibition, in conscious, hypertensive, transgenic ((mRen-2)27) rats (TG rats) and normotensive, Hannover Sprague-Dawley (SD) rats. 2 The hypotensive response to acetylcholine was greater in TG than in SD rats, but the renal vasodilator responses were not dierent. 3 The responses to bradykinin were similar in the two strains, except that hindquarters vasodilatation occurred onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…These findings suggest that prehypertensive TGR exhibit an enhanced NO activity in the systemic vasculature but a relative independency of the intrarenal vascular tone on NO. This concept is supported by observations by Gardiner et al [20,21] who demonstrated that there is no evidence for an increased NO activity in TGR compared with HanSD and that NO does not act as a buffer to antagonize the vasoconstrictor actions of ANG II. In accordance with previous findings that responses of urine flow and sodium excretion to NOS inhibition are influenced by the concomitant increases in BP [11][12][13][14], i.e.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These findings suggest that prehypertensive TGR exhibit an enhanced NO activity in the systemic vasculature but a relative independency of the intrarenal vascular tone on NO. This concept is supported by observations by Gardiner et al [20,21] who demonstrated that there is no evidence for an increased NO activity in TGR compared with HanSD and that NO does not act as a buffer to antagonize the vasoconstrictor actions of ANG II. In accordance with previous findings that responses of urine flow and sodium excretion to NOS inhibition are influenced by the concomitant increases in BP [11][12][13][14], i.e.…”
Section: Discussionsupporting
confidence: 73%
“…On the other hand, it has been shown that acute NOS inhibition elicited similar BP responses in TGR and HanSD [20,21]. In addition, reduced endotheliumdependent vasorelaxation has been reported in aortic ring preparations from male TGR [22].…”
Section: Introductionmentioning
confidence: 87%
“…In the second part of the study, we chose to infuse the NOS inhibitors, and compare their effects on a range of vasodilators, some of the responses to which we have previously shown to be influenced by L ‐NAME (Gardiner et al ., 1991b; 1992; 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The order of administration was randomised between animals within the groups, with at least 10 min between each substance to allow return to baseline values. The doses of vasodilators were chosen on the basis of previous experiments (Gardiner et al ., 1991b; Randall et al ., 1996; Gardiner et al ., 1998), which showed that they produced robust, steady‐state responses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation